Continuance Intention Pada Aplikasi Mobile Payment Dengan Menggunakan Extended Expectation Confirmation Model - M. Yahya Ubaidillah; Edwin Pramana; Francisca Haryanti Chandra (Sekawan Institut, 2023)
This study aims to identify the factors that influence the intention to continue using the mobile payment application during the new normal period after the COVID-19 pandemic, using the Extended Expectation Confirmation Model (EECM) approach. EECM combines aspects of the Expectation Confirmation Model (ECM) with other external factors, ECM is used to understand and explain decision-making related to the continued use of mobile payments. This research was conducted by analyzing data from respondents who have used mobile payment applications after the pandemic. The data was collected through an online survey and analyzed using Structural Equation Modeling (SEM) with the help of Analysis of Moment Structures (AMOS) software, 406 individuals were selected to serve as research participants. The results of the analysis show that factors such as satisfaction, and trust have a significant influence on the continuance intention of mobile payments. In addition, in the context of the new normal, factor such as social influence factors are known to have no significant influence on mobile payment continuance intention. As a result, this research contributes to understanding the factors that influence the intention to continue using mobile payment applications. The validity and reliability test results show that the survey instrument used has an adequate level of validity and reliability, supporting the quality and reliability of the analysis conducted.